Peranan Etika Kerja Islam Terhadap Hubungan Locus of Control dengan Kinerja Karyawan - Ridwan, R (Jurnal Trikonomika, 2013)
This studyâs objectives to asses moderating effect of Islamic work ethic variable to relationship in between locus of control with employers performance. The asses used Simple linear regression and Moderating Regression Analysis (MRA). Census method was used this study which included 32 responden from PT Bank Muamalat Indonesia Tbk. Cabang Palu employers. Result of the study indicated significantly effect of Islamic work ethic from relationship between locus of control to employers performance. Interaction coeficient marked negatif with significant Ï about 0.014 (Ï < 0.05) that it mind variable of islamic work ethic would be moderating variable which its fungtion diluted relationship locus of control to employers performance. Therefore, it need carefully to handle Islamic work ethic of employers if want to improve their performance by locus of control percieved.